FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI - Wiegianto, Jessica Alvon; Surjadi, Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to examine and analyze whether there is an influence between asset structure (tangibility), profitability, liquidity, and firm size on the asset structure of manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2020 period. In this research, there are 80 companies that will be studied by having a total of 240 data. This company uses secondary data in the form of company financial statements taken from the website www.idx.co.id. The sample selection in this study used a purposive sampling method and the data testing technique used multiple linear analysis processed using EViews 12. The results of the research that have been conducted indicate that the asset structure (tangibility) and profitability have no effect on capital structure while liquidity has a significant negative effect on capital structure and firm size have a positive and significant effect on capital structure.